Correlations between aesthetic preferences of river and landscape characters - Zhao, Jingwei; Luo, Pingjia; Wang, Ronghua; Cai, Yongli (Journal of Environmental Engineering and Landscape Management, 2013)
Some landscape characters put great influences on the aesthetic preferences of a river. Finding out these characters will provide for river landscape design and management with explicit keystones. In this paper, 23 sample areas of rivers were selected in Xuzhou, China, and 15 landscape characters of rivers were identified. The photos taken at the sample areas were as stimuli, and undergraduate students were respondents. The results demonstrate that the aesthetic preferences of photos judged one-by-one and judged together receive similar results; the preference scores of deflective views are significantly higher than the ones of opposite views; for urban rivers, “river accessibility” and “number of colours” are reliably positive predictors to aesthetic preferences, “wood diversity index” and “plants on water” are negative ones; for rural rivers, “coverage of riparian vegetation”, “perspective” and “wood diversity index” are reliably positive predictors to aesthetic preferences.First published online: 14 Dec 2012